HORMON YANG BERPERAN DALAM PEMBENTUKAN SPERMATOZOA DAN OVUM - I Gusti Ngurah Puger (Universitas Panji Sakti, 2022)
Abstract Normal men after stepping into the adolescent phase, they must produce sperm. Likewise, normal women after reaching the adolescent phase, they must produce ovum. However, there are still many men and women who have produced sperm or ovum and do not know about the hormones that affect on producing sperm or ovum. In males, the hypothalamus secretes releasing factors and stimulates the anterior pituitary gland to produce follicle stimulating hormone (FSH) and interstitial cell stimulating hormone (ICSH). The combination of FSH and ICSH will stimulate the testes to produce the hormone testosterone. The hormone testosterone is responsible for sperm production, penis growth, facial hair, and widening of the shoulders. In women, the hypothalamus secretes releasing factors and stimulates the anterior pituitary gland to produce follicle stimulating hormone (FSH) and luteinizing hormone (LH). FSH stimulates young follicles until they become mature follicles. Mature follicles due to the influence of luteinizing hormone will rupture, so that the ovum is released from the follicle. Follicles that no longer contain ovum will turn into a corpus luteum. The corpus luteum then produces the hormones progesterone and estrogen to keep the corpus luteum from being damaged.Keywords: Hormones, sperm formation, and ovum formation.